The Biological Mechanisms and Behavioral Functions of Opsin-Based Light Detection by the Skin - Kelley, Jennifer L.; Davies, Wayne I. L. (Frontiers in Ecology and Evolution, 2016)
Light detection not only forms the basis of vision (via visual retinal photoreceptors), but can also occur in other parts of the body, including many non-rod/non-cone ocular cells, the pineal complex, the deep brain, and the skin. Indeed, many of the photopigments (an opsin linked to a light-sensitive 11-cis retinal chromophore) that mediate color vision in the eyes of vertebrates are also present in the skin of animals such as reptiles, amphibians, crustaceans and fishes (with related photoreceptive molecules present in cephalopods), providing a localized mechanism for light detection across the surface of the body. This form of non-visual photosensitivity may be particularly important for animals that can change their coloration by altering the dispersion of pigments within the chromatophores (pigment containing cells) of the skin. Thus, skin coloration may be directly color matched or “tuned” to both the luminance and spectral properties of the local background environment, thereby facilitating behavioral functions such as camouflage, thermoregulation, and social signaling. This review examines the diversity and sensitivity of opsin-based photopigments present in the skin and considers their putative functional roles in mediating animal behavior. Furthermore, it discusses the potential underlying biochemical and molecular pathways that link shifts in environmental light to both photopigment expression and chromatophore photoresponses. Although photoreception that occurs independently of image formation remains poorly understood, this review highlights the important role of non-visual light detection in facilitating the multiple functions of animal coloration.